2022
DOI: 10.1111/ijag.16606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure in barium disilicate glass investigated by DTA and Raman spectroscopy

Abstract: This work aimed to explore the effect of high pressures at room temperature on the vibrational modes and the thermal properties and stability of barium disilicate glass (BaO‐2SiO2) (BS2). The BS2 was prepared through the conventional melting route at atmospheric pressure. After being submitted to different pressure values (2.5 GPa, 4.0 GPa, and 7.7 GPa) and room temperature, the samples were characterized ex situ by Raman spectroscopy and differential thermal analysis. With this, it is possible to see that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It can be seen from curve a of Figure that the bands at 604 and 498 cm –1 are ascribed to the three and four cyclosiloxane rings, respectively. The bands at 814 and 985 cm –1 could be assigned to Si–O–Si symmetrical stretching of the DMSN support and surface Si–OH stretching vibrations, respectively. For the 0.1Mo/DMSN and 0.5Mo/DMSN catalysts, the band at 978 cm –1 was ascribed to surface di-oxo (OMoO) species. The progressive shift of this band from 978 to 994 cm –1 was presumably attributable to the increased distortion caused by the lateral interactions between adjacent surface MoO x species with low Mo loading ( x ≤ 5.0).…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from curve a of Figure that the bands at 604 and 498 cm –1 are ascribed to the three and four cyclosiloxane rings, respectively. The bands at 814 and 985 cm –1 could be assigned to Si–O–Si symmetrical stretching of the DMSN support and surface Si–OH stretching vibrations, respectively. For the 0.1Mo/DMSN and 0.5Mo/DMSN catalysts, the band at 978 cm –1 was ascribed to surface di-oxo (OMoO) species. The progressive shift of this band from 978 to 994 cm –1 was presumably attributable to the increased distortion caused by the lateral interactions between adjacent surface MoO x species with low Mo loading ( x ≤ 5.0).…”
Section: Resultsmentioning
confidence: 99%
“…Subjecting a glass to high pressures (HPs) can lead to changes in all properties of the said material, as it has been noticed in several studies with lithium disilicate, [3][4][5][6] where ex situ nucleation rates decreased 3 and it presented polyamorphism after HP processing up to 7.7 GPa, 4 in situ crystallization created different crystalline phases than those obtained in atmospheric pressure, 5,6 and that crystal growth is suppressed when it was subjected to pressures up to 6.0 GPa due to an increase in viscosity, 7 and with barium disilicate, where also different crystalline phases were obtained from HP crystallization up to 7.7 GPa, 8 Raman vibrational modes remain constant after HP processing; however, thermal stability has changed to higher values than pristine glass. 9 In situ (up to 19 GPa) Raman analysis of glasses from the soda-lime-silica system showed modifications in the spectra; however, after decompression, the recovery was almost absolute. 10 In a previous work with the Na 2 O • 2CaO • 3SiO 2 (N 1 C 2 S 3 ) composition with in situ crystallization, it has been identified that the crystalline phase obtained is the same, the combeite, and it is stable with pressure up to 7.7 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…The Saad–Poulain factor 27 is defined as S0.33em=0.33em(Tc0.33em0.33emTx)(Tc0.33em0.33emTg)Tg$S\ = \ \frac{{( {{T}_c\ - \ {T}_x} )( {{T}_c\ - \ {T}_g} )}}{{{T}_g}}$, which can be rewritten with the term H0.33em=0.33emTc0.33em0.33emTgTg$H^{\prime}\ = \ \frac{{{T}_c\ - \ {T}_g}}{{{T}_g}}$ as S0.33em=0.33emH(Tc0.33em0.33emTx)$S\ = \ H^{\prime}( {{T}_c\ - \ {T}_x} )$, 28 whereas the S parameter indicates the stability of the glass (higher values means a more stable glass), and Tc0.33em0.33emTx${T}_c\ - \ {T}_x$ is associated with the energy required for crystallization 27 . Thermal analysis of glasses previously subjected to HP up to 7.7 GPa has been studied before 3,9 . In these works, it has been noted that HP can cause changes in T g and the S and H′ parameters of the glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation